PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN KOMPUTER DALAM MENDUKUNG PERKULIAHAN METROLOGI - Wagiran, Wagiran (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2018)
This study aimed at planning, constructing, and examining a computer-based learning media to support the implementation of constructivist learning in the metrology subject matter. The study used the Research and Development (R&D) approach. The research stages included: (1) competencies identification, (2) literature review, (3) software development, (4) quality testing, (5) empirical testing, (6) monitoring, (7) software revision, and (8) recording the program. Quantitative data were collected by means of observation sheets, depth interview, and documentation. Data were analyzed using the descriptive quantitative analysis technique. The results showed that: (1 the quality of the developed media was 73, 13 % (good), (2) the quality of program presentation was at 72, 66 % (good), and (3) the result of student testing was 76, 14 % (good). It was concluded that the developed media was appropriate for use in teaching and learning activities.